Direct CO2 capture and conversion to fuels on magnesium nanoparticles under ambient conditions simply using water. Issue 16 (31st March 2021) - Rawool, Sushma A.; Belgamwar, Rajesh; Jana, Rajkumar; Maity, Ayan; Bhumla, Ankit; Yigit, Nevzat; Datta, Ayan; Rupprechter, Günther; Polshettiwar, Vivek
Abstract : We demonstrated the use of magnesium nanoparticles (and bulk) to convert CO2 (pure & also from the air) to methane, methanol, formic acid and green cement without external energy within a few minutes, using only water as the sole hydrogen source. Abstract : Converting CO2 directly from the air to fuel under ambient conditions is a huge challenge. Thus, there is an urgent need for CO2 conversion protocols working at room temperature and atmospheric pressure, preferentially without any external energy input. Herein, we employ magnesium (nanoparticles and bulk), an inexpensive and the eighth-most abundant element, to convert CO2 to methane, methanol and formic acid, using water as the sole hydrogen source. The conversion of CO2 (pure, as well as directly from the air) took place within a few minutes at 300 K and 1 bar, and no external (thermal, photo, or electric) energy was required. Hydrogen was, however, the predominant product as the reaction of water with magnesium was favored over the reaction of CO2 and water with magnesium. A unique cooperative action of Mg, basic magnesium carbonate, CO2, and water enabled this CO2 transformation. If any of the four components was missing, no CO2 conversion took place. The reaction intermediates and the reaction pathway were identified by 13 CO2 isotopic labeling, powder X-ray diffraction (PXRD), nuclear magnetic resonance (NMR) and in situ attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR), and rationalized by density-functional theory (DFT) calculations. During CO2 conversion, Mg was converted to magnesium hydroxide and carbonate, which may be regenerated. Our low-temperature experiments also indicate the future prospect of using this CO2 -to-fuel conversion process on the surface of Mars, where CO2, water (ice), and magnesium are abundant. Thus, even though the overall process is non-catalytic, it could serve as a step towards a sustainable CO2 utilization strategy as well as potentially being a first step towards a magnesium-driven civilization on Mars.